1979
DOI: 10.4039/ent1111299-11
|View full text |Cite
|
Sign up to set email alerts
|

FACTORS AFFECTING THE MORTALITY OF LEAFMINERS ARGYRESTHIA THUIELLA AND PULICALVARIA THUJAELLA (LEPIDOPTERA: YPONOMEUTIDAE AND GELECHIIDAE) ON EASTERN WHITE CEDAR, IN ONTARIO

Abstract: Can. ~n t .11 1: 1293-1298 (1979) Elemental profiles of onion maggots reared on a dried carrot based medium were monitored by X-ray energy spectrometry. Adult insects had higher levels of S, Fe, Cu, and Zn and lower levels of C1, K, Br, and Sr than were apparently present in the medium. Addition of Rb to the larval diet resulted in a higher than normal concentration of Rb in the newlyemerged adults. This concentration of Rb decreased to ambient levels after 10 days. When Y was added to the rearing medium, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…In Quebec, Canada, Juillet (1972) recorded 26 species of parasitoids collectively destroying 50% of several species of arborvitae leafminers. In addition, a study by Bazinet and Sears (1979) found seven parasitoids species caused 9%-18% mortality of ALM, but their impact was reduced due to 63% winter-related mortality in 1977.…”
Section: Host Plant Characteristicsmentioning
confidence: 99%
“…In Quebec, Canada, Juillet (1972) recorded 26 species of parasitoids collectively destroying 50% of several species of arborvitae leafminers. In addition, a study by Bazinet and Sears (1979) found seven parasitoids species caused 9%-18% mortality of ALM, but their impact was reduced due to 63% winter-related mortality in 1977.…”
Section: Host Plant Characteristicsmentioning
confidence: 99%